Reflexões de um professor de literatura sobre o ensino - Antunes, Benedito [UNESP] (Universidade Federal de Goias, 2023)
This paper presents and discusses the book Sobre o ensino de literatura, by Paulo Franchetti (2021) so as to point out concepts, methods and political perspectives related to activities carried out with literature in classroom. Although this paper is concentrated on ideas and proposals made by the book, it also tries to relate, directly or indirectly, its main formularizations to a current discussion within the field of studies on literature teaching. Following the book own scheme, the subject will be broached both at Grade/Junior High School and Higher Education levels, or, inversely, from the literature teacher’s background development up to his/her professional performance.